Excitation of gravity modes in the parameter space of the tidal wind system (II): Magnetic effects - Blanco, S. (2000)
The Navier-Stokes, continuity and energy balance equations including magnetic effects for an inviscid compressible fluid in the ionospheric F-region were perturbed around the tidal phenomenological solution. We imposed adiabaticity and incompressibility to the perturbation. Our results satisfy the internal gravity wave (IGW) dispersion relation. The stable and unstable regions of these modes were derived as a function of two control parameters, the colatitude θ and the slow time evolution for tidal modes τ. These regions were obtained for different values of the magnetic field intensity, showing good agreement with observational data for the South Atlantic anomaly. Our model predictions for other magnetic field intensities corresponding to other latitude dependences need to be contrasted with new observational data. In addition we show for some hours and latitudes that, resonant interaction occurs between low frequency tidal waves and two high frequency gravity waves. In these regions, where tidal modes are linearly unstable, the gravity group velocity is modulated by a function of the tidal phase velocity.